2022
DOI: 10.3389/fmed.2022.802719
|View full text |Cite
|
Sign up to set email alerts
|

Application of Metagenomic Next-Generation Sequencing in Mycobacterium tuberculosis Infection

Abstract: The fight against Mycobacterium tuberculosis (MTB) has been going on for thousands of years, while it still poses a threat to human health. In addition to routine detections, metagenomic next-generation sequencing (mNGS) has begun to show presence as a comprehensive and hypothesis-free test. It can not only detect MTB without isolating specific pathogens but also suggest the co-infection pathogens or underlying tumor simultaneously, which is of benefit to assist in comprehensive clinical diagnosis. It also sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…Despite its potential, mNGS may have reduced sensitivity in paucibacillary specimens, resulting in a low yield of genomic DNA available for sequencing. mNGS has demonstrated success in diagnosing MTB in various specimens, including pulmonary, cerebrospinal fluid, and other extrapulmonary specimens [ 36 , 37 ]. Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its potential, mNGS may have reduced sensitivity in paucibacillary specimens, resulting in a low yield of genomic DNA available for sequencing. mNGS has demonstrated success in diagnosing MTB in various specimens, including pulmonary, cerebrospinal fluid, and other extrapulmonary specimens [ 36 , 37 ]. Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that mNGS is more suitable when the patient presents with unexplained manifestations beyond traditional assays or atypical symptoms, such as fever, dyspnea, and elevated inflammatory markers. It is also recommended when there is a strong suspicion of a multipathogen infection, in cases where the patient is in critical condition, and when timely and comprehensive detection results are crucially needed ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The advent of next-generation sequencing (NGS) techniques brings a new opportunity for the detection of mycobacterial nucleic acids [58,59]. The limitations of previous-generation sequencing techniques [60] did not allow the use of sequencing as a routine method for mycobacterial detection.…”
Section: Next-generation Sequencingmentioning
confidence: 99%
“…Like other mycobacterial nucleic acids detection techniques, NGS techniques have diagnostic applications. The technology is useful to identify the species or strains involved in a disease and can provide information about possible drug resistances [59].…”
Section: Next-generation Sequencingmentioning
confidence: 99%